Program of Rehabilitation and Functional Performance of Patients with Parkinson Disease Naval Medical Center “Cirujano Mayor Santiago Távara” - Díaz-Meyzan, LesLy (2021)
Objective. To determine the association between the application of the Rehabilitation Program (RP) and the Functional Performance (DF) of patients with Parkinson's disease at the "Cirujano Mayor Santiago Távara" Naval Medical Center. Methods. Analytical, longitudinal, retrospective cohort study, in 18 months. By means of a sample of 46 patients, in two cohorts, functional performance was determined by dimensions of basic activities (Barthel indexes), strength and endurance (SPPB) and walking speed. Five values or categories were used to determine dependency, frailty and incoordination. Normality was determined using the Kolmogorov-Smirnov test and for statistical analysis the Mann- Whitney U was used, where a value of p <0.05 was considered significant. Results. The mean age of patients was 79 +/- 3 years (range: 76-82) of the exposed cohort and 72 +/- 3 years (69-75) of the cohort not exposed to RP, 33 (71.7 %) were male of the total sample. 54.3 % (25) had one or more falls and in 45.65 % (21) their caregiver was a family member. There was a direct association between RP and DF (p=0.009) and in its dimensions: basic activities (p=0.001), strength and endurance (p=0.001) and walking speed (p=0.001). The cohort or group exposed to PR improved in autonomy, independence, endurance and balance in relation to the group not participating in PR. Conclusions. There is a direct association between PR and DF in all its dimensions: basic activities, strength, endurance and walking speed. The longer the duration of the RP, the better the DF.